Fiscal capacity in non-democratic states: The origins and expansion of income tax - Per F. Andersson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The origins of fiscal capacity have traditionally been linked to warfare and democratization. However, non-democratic states also invest in fiscal capacity, even in times of peace. In fact, the majority of income taxes-a cornerstone of government finance-were introduced by non-democratic states in peacetime. This paper is concerned with how autocratic politics shape fiscal capacity. Political institutions in non-democratic states help overcome a commitment problem related to investments in taxation. In order not to risk being deposed by his or her elite supporters, a ruler needs to guarantee that new fiscal tools will not be used opportunistically (e.g. for expropriation of the elite). If the elite supporters can effectively monitor the government, any transgressions will be detected and punishable. Institutions such as legislatures solve commitment problems related to investments in fiscal capacity when they allow oversight and monitoring over the executive branch. The empirical implications are straightforward: in places with strong institutional oversight, which allows the elite to monitor the executive, we should observe higher fiscal capacity. I find support for this notion by analysing newly available historical datasets over tax revenues, tax introduction dates, and political institutions.
Keywords: D78; H24; N40; P16; 330; fiscal capacity; autocratic politics; income tax